2017
DOI: 10.1103/physrevc.96.064613
|View full text |Cite
|
Sign up to set email alerts
|

Kaon femtoscopy in Pb-Pb collisions at sNN=2.76 TeV

Abstract: We present the results of three-dimensional femtoscopic analyses for charged and neutral kaons recorded by ALICE in Pb-Pb collisions at √ s NN = 2.76 TeV. Femtoscopy is used to measure the space-time characteristics of particle production from the effects of quantum statistics and final-state interactions in two-particle correlations. Kaon femtoscopy is an important supplement to that of pions because it allows one to distinguish between different model scenarios working equally well for pions. In particular, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 78 publications
2
5
0
Order By: Relevance
“…Comparing kaon and pion points, one can see the approximate k T scaling between two dependencies at k T > 0.4 GeV/c, repeating the behavior observed for the collisions at √ s NN = 2.76 TeV and noticed in iHKM simulations [19] prior to the experimental confirmation in Ref. [20]. In Figs.…”
Section: Results For √ S Nn = 502 Tev and Discussionsupporting
confidence: 84%
“…Comparing kaon and pion points, one can see the approximate k T scaling between two dependencies at k T > 0.4 GeV/c, repeating the behavior observed for the collisions at √ s NN = 2.76 TeV and noticed in iHKM simulations [19] prior to the experimental confirmation in Ref. [20]. In Figs.…”
Section: Results For √ S Nn = 502 Tev and Discussionsupporting
confidence: 84%
“…The EPOS 3 calculations for the radii without the cascade exhibit practically no k T dependence and do not describe the data, while the data are well reproduced by the full EPOS 3 model calculations thereby showing the importance of the hadronic cascade phase at LHC energies. This observation agrees with the conclusion from the threedimensional K ± femtoscopic analysis in Pb-Pb collisions at √ s NN = 2.76 TeV [47] where the hydrokinetic model HKM [56] with the hadronic rescattering phase described the charged kaon femtoscopic radii well. The extracted experimental λ values are about 0.45, whereas the EPOS 3 ones are about 0.65, i.e., apparently larger than the experimental λ values.…”
Section: Resultssupporting
confidence: 91%
“…The obtained correlation function C raw was also corrected for purity before the fit [14,47] according to…”
Section: Analysis Techniquementioning
confidence: 99%
“…In the last few years, there has been remarkable progress in studies of baryon-baryon interactions, both experimentally and theoretically. In particular, it was demonstrated that the momentum correlations between a pair of hadrons produced in heavy-ion collisions depend on quantum statistical effects and the space-time structure of the emitting source [29][30][31][32][33][34][35][36][37], in addition to being sensitive to the final-state interactions of the emitted hadron pair [38][39][40][41][42]. Because of the abundant hyperons produced in relativistic heavy-ion collisions and the excel-lent capabilities of detectors to identify particles and measure their momenta, the measurements of momentum correlation functions have become invaluable in revealing the precise dynamics of the strong interactions between a pair of hadrons, including meson-meson [43][44][45][46][47], meson-baryon [48][49][50], and (anti)baryon-(anti)baryon [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] interactions.…”
Section: Introductionmentioning
confidence: 99%